A project feasibility study on Good exchange - Causapin, Mark Gabriel A.; So, Sheryl Lyn M.; Terrel, Joseph L. (Diliman, Quezon City College of Engineering, 2001)
The sudden emergence of a second-hand industry in different parts of the world is due to the society's trend to be frugal. In line with this, the paper discusses the feasibility of Good Exchange, a second hand center, which will be pioneered in Metro Manila. To establish its market feasibility, surveys were conducted to determine the responses of potential customers and the products the customers are interested in selling and buying. Results show that there is a market for second hand products and the top three products they are most willing to sell and buy are furniture, clothes and books, respectively. It was also found that one branch of Good Exchange would be able to capture at least 17% of the market provided that a good promotions strategy be executed. In order to determine the company?s technical feasibility, a system was designed for the company to identify the procedures needed for gathering, processing and storing second hand materials. After which, the manpower, equipment and facilities requirements were computed in order to meet the targeted demand. It was found out that that a total of 42 workers and two trucks were needed in one branch and that the resources needed by the company are available. In the financial aspect, the investment and operating costs were computed, as well as the corresponding revenues in order to prepare the financial statements for the company. It was proven that Good Exchange is good investment opportunities due to its increasing profit levels every year and relatively good financial ratios. And finally, the social profitability of the company was studied by naming all the benefits, disadvantages and costs. Results show that Good Exchange generates income for the government in the form of tax payments, for its employees - composed of salaries, bonuses, trainings, etc. and that it helps the country by encouraging recycling of materials. In conclusion, Good Exchange was proven to be feasible in four aspects: market, technical, financial and social.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Good Exchange; Commodity exchanges; Speculation; Participatory monitoring and evaluation (Project management)